Linguistic Purism in the Germanic Languages - Davies, Winifred V.; Langer, Nils (W. de Gruyter, 2011)
Biographical note: Nils Langer is a Lecturer in German Linguistics at the University of Bristol, UK. Winifred Davies is a Senior Lecturer in German at the University of Wales Aberystwyth, UK.
Includes bibliographical references and indexes
Keywords: Konferenzschrift -- 2003 -- Bristol; Sprachpurismus; Germanische Sprachen